3-Methyl-4, 5-dihydro-oxepine, polyoxygenated seco-cyclohexenes and cyclohexenes from Uvaria flexuosa and their anti-inflammatory activity. (February 2016) - Hsu, Yu-Ming; Wu, Tung-Ying; Du, Ying-Chi; El-Shazly, Mohamed; Beerhues, Ludger; Thang, Tran Dinh; Van Luu, Hoang; Hwang, Tsong-Long; Chang, Fang-Rong; Wu, Yang-Chang
Graphical abstract: 3-Methyl-4, 5-dihydro-oxepine (1 ), four polyoxygenated seco-cyclohexenes (2 –5 ) and two polyoxygenated cyclohexenes (6 –7 ), along with four known compounds, were isolated from Uvaria flexuosa . Highlights: A rare 3-methyl-4, 5-dihydro-oxepine derivative was isolated from Uvaria flexuosa . Isolation of four seco-cyclohexenes with a characteristic skeleton from Uvaria sp. Two cyclohexenes were isolated with promising antiinflammatory activity. Benzyl alcohol benzoyl transferase is a key enzyme in the biosynthesis of these isolates. Abstract: The phytochemical investigation of the methanolic extract of Uvaria flexuosa (Annonaceae) leaves led to the isolation of seven compounds including, 3-methyl-4, 5-dihydro-oxepine (flexuvaroxepine A), four polyoxygenated seco-cyclohexene (flexuvarin A–D) and two polyoxygenated cyclohexene (flexuvarol A–B) derivatives, together with four known flavones. The structures of the isolated compounds were elucidated using different spectroscopic techniques. A plausible biogenetic route of the new compounds was discussed. The anti-inflammatory activity of the isolated compounds was evaluated by superoxide anion generation and elastase release assays. Among the tested compounds, flexuvarol B and chrysin showed the most potent anti-inflammatory effect by inhibiting superoxide anion generation and elastase release from human neutrophils in response to fMLP with IC50 2.25–5.55 μM. Moreover, 5-hydroxy-6, 7-dimethoxy-flavone showed selective inhibitory activity on superoxide anion generation (IC50 = 1.19 ± 0.34 μM).